MENYOAL GAMBARAN MANUSIA NASIONALIS INDONESIA MELALUI NOVEL MOCHTAR LUBIS - Nurweni Saptawuryandari (Kantor Bahasa Provinsi Maluku Utara, 2022)
Questioning the Image of Indonesian Humans Through Mochtar Lubis' Novels Abstract A writer writes literary works, among other things, to convey life models that are idealized and displayed in stories through characters. Through literary works, a writer offers moral messages related to the noble qualities of humanity, fighting for human rights and dignity. These qualities are essentially universal, it means believed by all humans. Mochtar Lubis through the novels Maut dan Cinta and Senja di Jakarta revealed a picture of humans with various problems. Regarding this issue, the purpose of this paper is to reveal the way Mochtar Lubis describes the image of Indonesian nationalist people, who love their homeland and their own nation. The human is depicted through the characters or ideas in the two novels. Disclosure of these problems will reveal the theory of structuralism so that it can be seen how the picture of people is. The used method is descriptive qualitative. The research data is literature. From the search results, it is found that the image of Indonesian nationalist people idealized and expressed in both novels is a picture of Indonesian nationalist people who are dignified, noble in character, and have a sense of nationalism and nationality towards their nation. Keywords: description, Indonesian nationalist, structuralism